A novel RT-multiplex PCR for enteroviruses, hepatitis A and E viruses and influenza A virus among infants and children with diarrhea in Vietnam - Phan, T. G.; Nguyen, T. A.; Yan, H.; Okitsu, S.; Ushijima, H. (Archives of virology, 2005)
A novel reverse transcription-multiplex polymerase chain reaction (RT-multiplex PCR) assay that can detect enteroviruses, hepatitis A and E viruses and influenza A virus from various hosts (avian species, human, swine and horse) was developed. The identification of that group of viruses was performed with the mixture of four pairs of published specific primers (F1 and R1, P3 and P4, 2s and 2as, MMU42 and MMU43) for amplifying viral genomes and specifically generated four different amplicon sizes of 440, 267, 146 and 219 bp for enteroviruses, hepatitis A and E viruses and influenza A virus, respectively. A total of 276 fecal specimens (previously screened for rotavirus, adenovirus, norovirus, sapovirus and astrovirus-negative) from infants and children admitted into hospital with acute gastroenteritis in Ho Chi Minh city, Vietnam during October 2002 and September 2003 were collected and further tested for the presence of those viruses by RT-multiplex PCR. Enteroviruses were identified in 27 specimens and this represented 9.8%. No hepatitis A and E viruses and influenza A virus was found among these subjects. The sensitivity and specificity of RT-multiplex PCR were also assessed and demonstrated the strong validation against RT-monoplex PCR. Taken together, the findings clearly indicated that this novel RT-multiplex PCR is a simple and potential assay for rapid, sensitive, specific and cost-effective laboratory diagnosis to investigate molecular epidemiology of acute gastroenteritis caused by enteroviruses, hepatitis A and E viruses and influenza A virus. This report is the first, to our knowledge, detecting these kinds of viruses in diarrheal feces from infants and children in Vietnam.